Le système monétaire européen : Le point de vue européen - Lelart, Michel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1981)
The evolution of the international monetary System prompted the nine members of the E.E.C. to establish a European Monetary System. The new statutes of the I.M.F. have in fact legalized the practice of flexible exchange rates and sanctioned the dollar's inconvertibility while eliminating the role of gold. Further, the increasing importance of the international capital markets fosters the unlimited expansion of international liquidities.it is in response to this context then that Europe seeks to create a zone of stability and to manage its own international tender in accordance with rules that it has set for itself. The author draws a positive conclusion as the System has operated without major problems so far. Nevertheless, difficulties remain: the international environment has not improved given the abrupt strengthening of the dollar and the increase in American interest rates. In addition, progress with regard to cooperation among the Nine remains slow and political change in France makes any prognosis respecting the future of the European Monetary System difficult.It was anticipated that the System would be Consolidated rapidly. It would in that event contribute more effectively to the stability of the international monetary System. It could, on the other hand, sharpen competition between Europe and the United States, between the Ecu and S.D.Rs. and between the European Monetary Fund and the International Monetary Fund.